2018
DOI: 10.1016/j.virol.2017.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Ebola virus requires phosphatidylinositol (3,5) bisphosphate production for efficient viral entry

Abstract: For entry, Ebola virus (EBOV) requires the interaction of its viral glycoprotein with the cellular protein Niemann-Pick C1 (NPC1) which resides in late endosomes and lysosomes. How EBOV is trafficked and delivered to NPC1 and whether this is positively regulated during entry remain unclear. Here, we show that the PIKfyve-ArPIKfyve-Sac3 cellular complex, which is involved in the metabolism of phosphatidylinositol (3,5) bisphosphate (PtdIns(3,5)P), is critical for EBOV infection. Although the expression of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 75 publications
6
62
0
Order By: Relevance
“…In 2019, orphan drug designation was granted to apilimod in the U.S. for the treatment of follicular lymphoma 88 , with phase I clinical trials ongoing. Notably, it has been reported that apilimod efficiently inhibits EBOV, Lassa virus (LASV), and Marburg virus (MARV) in human cell lines, underscoring its potential broad-spectrum antiviral activity 44,89 . The underlying mechanism for the inhibition of SARS-CoV-2 infection by apilimod is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…In 2019, orphan drug designation was granted to apilimod in the U.S. for the treatment of follicular lymphoma 88 , with phase I clinical trials ongoing. Notably, it has been reported that apilimod efficiently inhibits EBOV, Lassa virus (LASV), and Marburg virus (MARV) in human cell lines, underscoring its potential broad-spectrum antiviral activity 44,89 . The underlying mechanism for the inhibition of SARS-CoV-2 infection by apilimod is currently not known.…”
Section: Discussionmentioning
confidence: 99%
“…We began this study by comparing the ability of eight drugs to inhibit LASV and EBOV GP-mediated infection. All eight are orally available, room temperature-stable small molecules that block EBOV entry (18-20, 22, 23, 40, 50) and target entry processes also used by LASV (20)(21)(22)(23)(51)(52)(53). Six are approved for clinical use and two are in advanced clinical testing.…”
Section: Discussionmentioning
confidence: 99%
“…Both have been shown, albeit not in direct comparative studies, to inhibit many pathogens that enter cells by endocytosis (21)(22)(23)(57)(58)(59)(60). The fourth drug with similar activity against both viruses is apilimod, which inhibits PIKfyve, an enzyme required for late endosome maturation (51,53,61) and EBOV entry (27). Apilimod blocks EBOV trafficking to late endosomes (51, 53), which serve as portals for both EBOV and LASV (25, 26, 62-64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell entry of EBOV involves virus binding to the cell surface receptors followed by internalization through macropinocytosis, processing by endosomal proteases, and transport to Niemann–Pick C1 (NPC1; an internal receptor for EBOV) containing endolysosomes. Phosphatidylinositol-3-phosphate 5-kinase is essential for maturation of endosome, a critical step to the EBOV infection ( 145 ). In vitro studies using apilimod, an antagonist of phosphatidylinositol-3-phosphate 5-kinase, showed inhibition of EBOV by blocking the viral particle trafficking to NPC1 containing endolysosomes ( 146 ).…”
Section: Advances In Developing Drugs and Therapies Against Ebovmentioning
confidence: 99%